Sinergi Komunitas dalam Pembentukan Kelompok Pengrajin Sepatu Anak: Pelatihan berdampak terhadap Pembangunan Ekonomi Berkelanjutan - Minrohayati; Zainur Hidayah; Sri Lestari Pujiastuti; Moh Abdul Basir; ANDRIYANSAH, Andriyansah (Universitas Terbuka, 2025)
The establishment of a children's shoe artisan group aims to empower local communities and promote sustainable economic development. This study was conducted to evaluate the impact of skill training and business management on the capabilities of the artisan group. The methodology employed comprised six stages: exploration, group formation, skill training, mentoring, marketing, and evaluation. The results indicate a significant improvement in production and marketing skills among group members. Before the training, only 30% of participants possessed basic knowledge of production techniques, whereas after the training, this figure increased to 85%. Furthermore, the ability to utilize social media for marketing also rose from 20% to 75%. This training program has proven effective in creating high-quality products with aesthetic appeal while integrating local values and cultural wisdom. The synergy among group members and collaboration in product development enhance their competitiveness in the market. Thus, the formation of the children's shoe artisan group contributes to the improvement of the local economy, job creation, and the strengthening of regional cultural identity. Recommendations for the sustainability of the program include strengthening collaboration networks and ongoing innovation in product development. This research is expected to serve as a model for other communities to empower local economies and enhance community welfare.